Keanekaragaman Mikroalga sebagai Bioindikator di Perairan Sungai - Mustika Elmi Dayana; Abdul Rahman Singkam; Dewi Jumiarni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the diversity of microalgae and their relationship with water quality in the Air Lais River. The method used is a survey method. The results showed that there were 28 species of microalgae consisting of 7 divisions. The abundance of microalgae at the upstream station was 52 ind/ml, the middle station was 50 ind/ml and the downstream station was 115 ind/ml. The microalgae diversity index at each station was 2.2; 2.2; and 2.59, with a moderate level of diversity criteria. The microalgae dominance index was in the low dominance criteria, with the value of each station being 0.21; 0.20; and 0.14. In conclusion, the condition of the Air Lais River is still relatively clean and shows a normal tolerance range for microalgae life. Keywords: Diversity, Microalgae, Lais Water River